“I Shall Give Thee the Heathen for Thine Inheritance” - McGhee, Patrick S. (Exchange, 2025)
Taking the scriptural concept of the ‘heathen’ as its starting point, this article investigates the attitudes of Protestant ministers and parishioners in England towards the conversion of indigenous non-Christian people in colonial New England during the years of the English republic from 1649 to 1660. The article examines Psalm 2 as a framework within which churchgoers interpreted non-Christianity, before turning to the fragmentary prosopography of parishioners who donated money towards the cause of religious expansion. Illuminating the practical strategies that the new government developed as its pursuit of legitimacy intersected with attitudes towards evangelism overseas, the article demonstrates the ways in which liturgical, pastoral, political and socio-economic circumstances shaped local engagement with the wider Atlantic world. It suggests that English support for the propagation of the gospel emerged from profound theological ambivalence as animosity towards non-believers co-existed with the conviction that some among them could convert and might be saved.
EPrint Processing Status: Full text deposited in DRO